Individualized training model for junior trampoline competitors - Bronsky, E. V.; Lebedeva, V. I. (Theory and Practice of Physical Culture, 2019)
The study analyzes the design and benefits of an individualized theoretical and practical training model for junior (9-10 year-old) trampoline gymnasts having 2-year training records. The sample was split up into Experimental (EG, n=14) and Reference (RG, n=16) Groups for the model testing purposes. The model was intended to mobilize and cultivate progress motivations in the following aspects: individual physical qualities; physical fitness with an emphasis on the technical skills; gymnastics-styled execution etc. The study showed the individualized motivations-cultivating theoretical and practical training model being beneficial as verified by the pre- versus post-experimental progress test data of the EG versus RG, with the EG tested with significant (?<0.05-0.01) progress in the technical execution rated by 4.63 to 5,0 points (i.e. high and excellent) in 8 tests out of 11. The model was found to help mobilize the individual resources for progress in the theoretical and practical trainings to improve the competitive performance - more efficiently and effectively than the traditional training system.